Antidepressant Use in Medicaid-Insured Youth: Trends, Covariates, and Future Research Needs - Zito, Julie M.; Pennap, Dinci; Safer, Daniel J. (Frontiers in Psychiatry, 2020)
Background Detailed research on long-term antidepressant (AD) trends within a single large US Medicaid population of youth has not heretofore been reported. Methods Administrative claims data for eight annual timepoints across 28 years (1987–2014) were organized for youth (<20 years old) who were continuously enrolled during each study year in a mid-Atlantic state Medicaid program. Total annual AD prevalence and age-, gender-, race-, eligibility group-, and diagnosis-specific prevalence were formed from bivariate analyses; logistic regression assessed the change in use (2007–2014) adjusted for covariates. AD-polypharmacy data were assessed in 2014. Results The major findings are: 1) AD use in state Medicaid enrollees grew 14-fold between 1987 and 2014. Data from 2014 revealed significantly increased odds of youth with SSRI/SNRI dispensings compared to 2007 (AOR=1.15 95% CI 1.11–1.19), representing 78% of total AD users. 2) Recent AD increases were greatest for 15–19-year olds. 3) AD use in girls passed up AD use in boys for the first time in 2014. 4) In 2014, ADs for foster care (12.7%) were 6 times greater than for their income-eligible Medicaid-counterparts. 5) In 2014, a quarter of AD-medicated youth were diagnosed with a behavior disorder. 6) More than 40 percent of AD medicated youth had >=1 other concomitant psychotropic classes for 60 or more days. Conclusions Second-generation antidepressant use in Medicaid-insured youth has increased despite growing questions that pediatric AD benefits may not outweigh harms. These patterns support the call for publicly funded, independent investigator-conducted post-marketing outcomes research.